Pharmacological, Mechanistic, and Pharmacokinetic Assessment of Novel Melatonin-Tamoxifen Drug Conjugates as Breast Cancer Drugs - Hasan, Mahmud; Marzouk, Mohamed Akmal; Adhikari, Saugat; Wright, Thomas D.; Miller, Benton P.; Matossian, Margarite D.; Elliott, Steven; Wright, Maryl; Alzoubi, Madlin; Collins-Burow, Bridgette M.; Burow, Matthew E.; Holzgrabe, Ulrike; et al. (Molecular pharmacology, 2019)
Tamoxifen is used to prevent and treat estrogen receptor–positive (ER+) breast cancer (BC); however, its chronic use can increase uterine cancer risk and induce tamoxifen resistance. Novel melatonin-tamoxifen drug conjugates may be promising to treat BC and may help offset the adverse effects of tamoxifen usage alone due to the presence of melatonin. We synthesized and screened five drug conjugates (C2, C4, C5, C9, and C15 linked) for their effects on BC cell (MCF-7, tamoxifen-resistant MCF-7, mouse mammary carcinoma, MDA-MB-231, and BT-549) viability, migration, and binding affinity to melatonin receptor 1 (MT1R) and estrogen receptor 1 (ESR1). C4 and C5 demonstrated the most favorable pharmacological characteristics with respect to binding profiles (affinity for ESR1 and MT1R) and their potency/efficacy to inhibit BC cell viability and migration in four phenotypically diverse invasive ductal BC cell lines. C4 and C5 were further assessed for their actions against tamoxifen-resistant MCF-7 cells and a patient-derived xenograft triple-negative BC cell line (TU-BcX-4IC) and for their mechanisms of action using selective mitogen-activated protein kinase kinase MEK1/2, MEK5, and phosphoinositide 3-kinase (PI3K) inhibitors. C4 and C5 inhibited tamoxifen-resistant MCF-7 cells with equal potency (IC50 = 4–8 μM) and efficacy (∼90% inhibition of viability and migration) but demonstrated increased potency (IC50 = 80–211 μM) and efficacy (∼140% inhibition) to inhibit migration versus cell viability (IC50 = 181–304 mM; efficacy ∼80% inhibition) in TU-BcX-4IC cells. Unique pharmacokinetic profiles were observed, with C4 having greater bioavailability than C5. Further assessment of C4 and C5 demonstrates that they create novel pharmacophores within each BC cell that is context specific and involves MEK1/2/pERK1/2, MEK5/pERK5, PI3K, and nuclear factor κB. These melatonin-tamoxifen drug conjugates show promise as novel anticancer drugs and further preclinical and clinical evaluation is warranted.